An evaluation of blood components inventory management during Hajj and Umrah season at Makkah hospitals: Impact of Hajj and Umrah on Blood inventory - Kabrah, Saeed M (Journal of Contemporary Medical Sciences, 2022)
Objectives: The current study aims to utilize blood bank data collected from the Army forces hospital in Makkah to improve transfusion services at Makkah hospitals and evaluate the inventory system during the Hajj season. Methods: Three years' results showed that blood centre production is not constant, with an average of 1800 units during Hajj season that includes Cryo (450), FFP (450), PLT (450), and PRBC (450) units. Moreover, data indicated that the average usage of units is 1119 during the same season (120 Cryo, 424 FFP, 207 PLT and 368 PRBC). Results: This demonstrated that the inventory of blood units fluctuates during the year with an overproduction of Cryo (80%), FFP (67%), PLT (83%) and PRBC (57%) units in Hajj Season. It can be concluded that the manner and effectiveness with which the present issues in Makkah blood banking are having a major impact on the current system used to obtain the nation's blood supply and the safety, adequacy, and operational cost of that supply. Conclusion: The current study recommends building a generic data warehouse with smart decision support systems that use artificial intelligence to maintain blood bank production and inventory system during the year, especially during Hajj and Umrah seasons.